Formation and Surface Behavior of Pt and Pd Complexes with Ligand Systems Derived from Nitrile‐functionalized Ionic Liquids Studied by XPS. Issue 2 (17th January 2023) - Hemmeter, Daniel; Paap, Ulrike; Taccardi, Nicola; Mehler, Julian; Schulz, Peter S.; Wasserscheid, Peter; Maier, Florian; Steinrück, Hans‐Peter
Abstract: The front cover artwork is provided by the groups of Prof. Hans‐Peter Steinrück and Prof. Peter Wasserscheid at the Friedrich‐Alexander‐Universität (FAU) Erlangen‐Nürnberg. The image shows substitution of volatile acetonitrile ligands by a nitrile‐functionalized imidazolium cation. The formed cationic complex and the counter ions exhibit a specific preferential orientation at the ionic liquid/gas interface, which can be studied by angle‐resolved XPS. Read the full text of the Research Article at 10.1002/cphc.202200391 . Abstract : "We present the preparation of Pt and Pd complexes containing ligand systems derived from nitrile‐functionalized IL cations and their interfacial behavior in IL solution probed by angular‐resolved X‐ray photoelectron spectroscopy (ARXPS)…" This and more about the story behind the front cover can be found in the Research Article at 10.1002/cphc.202200391 .